Ni1.5CoSe5 nanocubes embedded in 3D dual N-doped carbon network as advanced anode material in sodium-ion full cells with superior low-temperature and high-power properties. Issue 45 (5th November 2018) - Wang, Ying-Ying; Fan, Haosen; Hou, Bao-Hua; Rui, Xian-Hong; Ning, Qiu-Li; Cui, Zheng; Guo, Jin-Zhi; Yang, Yang; Wu, Xing-Long
Abstract : An advanced anode for sodium-ion batteries is prepared by embedding cube-like Ni1.5 CoSe5 nanoaggregates into 3D dual N-doped carbon network. Abstract : In this study, the double transition metal selenide Ni1.5 CoSe5 with cube-like nanoaggregate morphology was successfully embedded into a three-dimensional (3D) dual N-doped carbon network, developing an advanced anode material for sodium-ion batteries (SIBs). In the prepared composite, Ni1.5 CoSe5 nanoparticles were first coated by N-doped carbon (NC), which further aggregated to form nanocubes, and finally embedded into interconnected N-doped reduced graphene oxide (rGO) nanosheets; hence, the material was abbreviated as Ni1.5 CoSe5 @NC@rGO. It delivered a reversible Na-storage capacity of 582.5 mA h g −1 at a low current density of 0.05 A g −1 and exhibited ultra-fast rate properties ( e.g., with the specific capacities of 180.8 and 96.3 mA h g −1 at high current densities of 30 and 50 A g −1, respectively). The much enhanced Na-storage properties were ascribed to the highly conductive 3D network constructed by dual N-doped carbonaceous materials, which acted not only as a highway for ultrafast charge transfer but also as an effective protector for the active Ni1.5 CoSe5 material and cube-like nanoaggregates with nanometer-sized primary particles. More significantly, the Ni1.5 CoSe5 @NC@rGO electrode also exhibited superior energy storage performance in sodium-ion full cells when coupled with a high-voltage Na3 V2 (PO4 )2 O2 F cathode, making it a promising anode material for practical SIBs.